2016
DOI: 10.1002/tcr.201500239
|View full text |Cite
|
Sign up to set email alerts
|

In VitroSelection Combined with Ribosomal Translation Containing Non-proteinogenic Amino Acids

Abstract: The potential applications of non-proteinogenic amino acids have increased continuously since the introduction of these molecules into a ribosomal translation system. An increasing number of studies concerning topics, such as the addition of an artificial function to a protein, cellular expression of a protein with an artificial residue, and development of an artificial peptide with a novel function, have been done using these molecules. Here, we describe recent studies that elucidate the compatibility of non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 82 publications
(141 reference statements)
0
8
0
Order By: Relevance
“…Additionally, β-amino acids receive attention as the building blocks of peptide analogues for pharmaceutical uses, because β-amino acids improve the stability of the peptide analogues containing them against proteolysis. , Our study greatly increased the knowledge for the use of β-amino acids in a ribosomal translation system, so it makes β-amino acids available for the construction of the peptide library. Such highly diverse peptide libraries containing β-amino acids would become a useful source for therapeutic peptidomimetics in the future. , …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, β-amino acids receive attention as the building blocks of peptide analogues for pharmaceutical uses, because β-amino acids improve the stability of the peptide analogues containing them against proteolysis. , Our study greatly increased the knowledge for the use of β-amino acids in a ribosomal translation system, so it makes β-amino acids available for the construction of the peptide library. Such highly diverse peptide libraries containing β-amino acids would become a useful source for therapeutic peptidomimetics in the future. , …”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the ribosome has a remarkable tolerance for various nonproteinogenic amino acids, although natural translation system commonly employs 20 proteinogenic α-amino acids as substrates. The ribosomal tolerance toward backbone-modified amino acids, such as N -methyl amino acids and d -amino acids, has been studied, but the results of these studies were partially inconsistent presumably because of the insufficient optimization of the cell-free translation systems to study the tolerance of ribosome. In the previous report, we successfully applied our optimized translation system to reveal d -amino acids compatibility with ribosomal translation, and found various d -amino acids that could be used for the ribosomal peptide synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of mutant E. coli ribosomes that enhance d -amino acid incorporation in vitro indicates potential for in vivo incorporation of d -amino acids . Similarly, in 2018, the Murakami lab improved incorporation of multiple β-amino acids, producing peptides with natural amino acid spacers between two or three β-amino acids in their optimized translation system . Translating the in vitro advances in incorporation of backbone analogue UAAs to cells should catch on as more suitable aaRS/tRNA pairs are established.…”
Section: A General Methods For the Site-specific Incorporation Of Uaa...mentioning
confidence: 99%
“…67 Similarly, in 2018, the Murakami lab improved incorporation of multiple β-amino acids, producing peptides with natural amino acid spacers between two or three β-amino acids in their optimized translation system. 68 Translating the in vitro advances in incorporation of backbone analogue UAAs to cells should catch on as more suitable aaRS/ tRNA pairs are established. In 2019, Dedkova and Hecht found that wild-type PylRS could incorporate a fluorescent oxazole UAA lacking an asymmetric center or α-amino group.…”
Section: Incorporation Of Uaas In Vivomentioning
confidence: 99%